Doing what we imagine: Completion rates and frequency attributes of imagined future events one year after prospection - Spreng, R. Nathan (2012)
Recent years have seen an explosion of studies examining behavioral and neural aspects of imagining future events. However, little is known whether imagined future events reflect future happenings. We examined event occurrence one year after participants imagined highly probable future events, specific to place and time. Overall, participants did engage in most of their imagined events. Completion rates were similar to naturalistic prospective memory and implementation intention studies examining personal plan completion. Approximately 20% of events were abandoned. We found participants often imagined events that were repeated many times in the course of a year and this impacted the vividness of recollection, sense of personal importance, personal involvement in event fulfillment, and extent of positive emotionality one year later. Together, the results provide an important validation for prospection research and highlight novel dimensions in the temporal structure of future-thinking.